The effect of handlebar height and bicycle frame length on muscular activity during cycling: a pilot study - Conceição, Ana (2022)
The cycling literature is filled with reports of electromyography (EMG) analyses for a better understanding of muscle function during cycling. This research is not just limited to performance, as the cyclist’s goal may be rehabilitation, recreation, or competition, so a bicycle that meets the rider’s needs is essential for a more efficient muscular activity. Therefore, the purpose of this study was to understand the contribution of the activity of each of the following muscles: TD (trapezius descending), LD (latissimus dorsi), GM (gluteus maximus), and AD (anterior deltoid) in response to different bicycle-rider systems (handlebar height; bicycle frame length) and intensities in a bicycle equipped with a potentiometer. Surface EMG signals from muscles on the right side of the body were measured. A general linear model test was used to analyze the differences between muscle activation in the test conditions. Effect sizes were calculated using a partial Eta2 (η 2 ). The level of significance was set at 0.05. Muscle activation of different muscles differs, depending on the cycling condition (Pillai’s trace = 2.487; F (36.69) = 9.300; p < 0.001. η 2 = 0.958), mostly during low intensities. In high intensities, one specific pattern emerges, with a greater contribution of GM and TD and weaker participation of LD and AD, enhancing the cycling power output.